Deforestation in mixed ombrophilous forest in the serrana region of santa catarina Desmatamento em floresta ombrófila mista na região serrana de santa catarina - Schneider L.C.A. (2018)
© 2018, Sociedade de Investigacoes Florestais. All rights reserved.Since the enactment of Law No. 11,428/06, an expectation was created as to whether more restricted rules on the use and conservation of the Atlantic Forest Biome would be sufficient to reduce deforestation. In the same sense, the inspection bodies stood out due to their responsibility in the application of this important legal instrument. In this context, the objectives of this study were: 1) to analyze the history of deforestation in the Planalto Serrano of the State of Santa Catarina, whose forest covered area is characterized by the Mixed Ombrophilous Forest, after the validity of Law 11,428/06; 2) to verify the application of the Law in the occurrence of deforestation, and 3) to identify the reasons for deforestation. A documentary research was carried out on 543 criminal procedures instituted by the Environmental Military Police for deforestation between December 2006 and December 2015. From each criminal case the following data were extracted: date, number of occurrences per year and municipality, size, successional stage of the deforested area, motive and land use of deforested areas. The results indicated that there was an accentuated reduction of 58% in the number of deforestation between 2007 and 2015. However, the selective cutting of Araucaria angustifolia (Bertol.) Kuntze was predominant with a percentage of 62.07% of the total number of occurrences. It was also verified that 71.46% of deforestation reached the middle stage of forest regeneration. In most case (33%), the reason for deforestation was for commercial purposes. The law for the protection of the Atlantic Forest Biome, conjunctly with the inspection, contributed to reduce deforestation and the cut of araucarias. Nevertheless, advancements are still needed, especially in the recovery of deforested areas, since only 28% of deforested areas were effectively restored.